2006
DOI: 10.1111/j.1469-1795.2006.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protection on nest take and nesting success of parrots in Africa, Asia and Australasia

Abstract: Wild parrots represent one of the greatest commercial interests in the legal trade in wild birds. Although it is difficult to quantify, there is a considerable illegal trade in wild parrots. Thirty-six per cent of the world's parrot species are listed by the International Union for the Conservation of Nature as threatened or near threatened, and 55% of these are threatened to some degree by trade. In this paper, we investigate the impact of protection on the number of nests that failed because of nestlings bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…Accurate statistics on the number of wild birds in illegal trade is not available and the number of birds removed from wild environments may be two to four times higher than that suggested by published data (Pain et al, 2006). Our results showed that, despite the intense persecution, Bluefronted Amazon genetic variability is comparable to that observed in non-traded species.…”
Section: Locimentioning
confidence: 38%
“…Accurate statistics on the number of wild birds in illegal trade is not available and the number of birds removed from wild environments may be two to four times higher than that suggested by published data (Pain et al, 2006). Our results showed that, despite the intense persecution, Bluefronted Amazon genetic variability is comparable to that observed in non-traded species.…”
Section: Locimentioning
confidence: 38%
“…Captive 50 breeding is a major source of individuals to supply aviculture markets, although only a small number of species are sourced from this industry [2]. The total impact of the illegal trade in birds is particularly challenging to quantify in numbers due to its clandestine nature, and the cumulative impact of the mortality rates during capture, transport and pre-and post-sale [2][3][4]. The detrimental impacts of such activities are 55 having a measurable effect on cockatoos and parrots in the wild, both in terms of biodiversity and population number [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The total impact of the illegal trade in birds is particularly challenging to quantify in numbers due to its clandestine nature, and the cumulative impact of the mortality rates during capture, transport and pre-and post-sale [2][3][4]. The detrimental impacts of such activities are 55 having a measurable effect on cockatoos and parrots in the wild, both in terms of biodiversity and population number [2,3]. Spix's macaw (Cyanopsitta spixii) is one of the most recent cases of extinction in the wild, caused by illegal harvest [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations